Pengaruh Kompensasi dan Konflik Kerja terhadap Turnover Intention Karyawan dengan Motivasi Kerja sebagai Variabel Intervening di PT Definite Maji Arsana Jakarta - Saharso, Saharso; Toyibah, Toyibah (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of study is to determine the influance of compensation and working conflict on turnover intention with job motivation as an intervening variable of PT Definite Maji Arsana. The population of this study were all empoyess of PT Definite Maji Arsana which amounted to 60 people. The hypothesis was tested in SmartPLS Software version 3.0, using Structural Equation Model (SEM) based on variant with the model of Partial Least Square (PLS). The results showed a significancy effect on all of the hypotheses. Compensation shows negative significancy effect on Employee Turnover Intention. Compensation shows positive significancy effect on Job Motivation. Work Conflict shows positive significancy effect on Employee Turnover Intention. Work Conflict shows negative significancy effect on Job Motivation. Job Motivation shows negative significancy effect on Employee Turnover Intention. Job Motivation proven to mediate the effect of Compensation on Employee Turnover Intention. Job Motivation proven to mediate the effect of Work Conflict on Employee Turnover Intention